Study of the anther hairs of eight taxa of the genus Chamaecrista Moench (Leguminosae) under SEM - Khatun, BM Rezia (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 77-80, 2003 (December)